Optimization of globomycin analogs as novel gram-negative antibiotics. Issue 20 (15th October 2020) - Garland, Keira; Pantua, Homer; Braun, Marie-Gabrielle; Burdick, Daniel J.; Castanedo, Georgette M.; Chen, Yi-Chen; Cheng, Yun-Xing; Cheong, Jonathan; Daniels, Blake; Deshmukh, Gauri; Fu, Yuhong; Gibbons, Paul; et al.
Graphical abstract: Abstract: Discovery of novel classes of Gram-negative antibiotics with activity against multi-drug resistant infections is a critical unmet need. As an essential member of the lipoprotein biosynthetic pathway, lipoprotein signal peptidase II (LspA) is an attractive target for antibacterial drug discovery, with the natural product inhibitor globomycin offering a modestly-active starting point. Informed by structure-based design, the globomycin depsipeptide was optimized to improve activity against E. coli. Backbone modifications, together with adjustment of physicochemical properties, afforded potent compounds with good in vivo pharmacokinetic profiles. Optimized compounds such as 51 (E. coli MIC 3.1 μM) and 61 (E. coli MIC 0.78 μM) demonstrate broad spectrum activity against gram-negative pathogens and may provide opportunities for future antibiotic discovery.